SXP01: a novel bacteriophage for combating Shewanella xiamenensis in aquaculture - Li, Chen; Zhang, Yangjun; Peng, Yuyuan; Zhang, Guofan; Xie, Jiajie; Long, Xinran; Qian, Linger; Hu, Yibo; Hu, Shengbiao (Frontiers in Microbiology, 2025)
IntroductionThe emergence of multi-drug resistant Shewanella xiamenensis poses a significant threat to aquaculture and public health, driving the need for alternative therapies like bacteriophages.MethodsA novel bacteriophage, SXP01, was isolated using S. xiamenensis A001 as a host. Its kinetic parameters (MOI, latent period) and stability across temperature (4-60°C), pH (6-11), and chloroform were characterized. The lysis cassette was identified genomically, and a recombinant endolysin (LysSXP-1) was expressed to test lytic activity. In vivo efficacy was evaluated in a crucian carp infection model.ResultsSXP01, a Myoviridae member, showed an optimal MOI of 0.1, a 20-minute latent period, and high environmental stability. Its lysis cassette encodes two endolysins, with LysSXP-1 demonstrating direct lytic activity. In the fish model, SXP01 treatment significantly increased survival rates from 13.3% to 56.7%.DiscussionThe study identifies SXP01 as a highly stable and effective bacteriophage. The synergistic action of its endolysins and its demonstrated in vivo efficacy highlight its strong potential as a targeted biocontrol agent to manage S. xiamenensis infections in aquaculture sustainably.